Discovery of H I gas in a young radio galaxy at z = 0.44 using the Australian Square Kilometre Array Pathfinder - Allison, J; Sadler, E; Moss, V; Whiting, M; Hunstead, R; Pracy, M; Curran, S; Croom, S; Glowacki, M; Morganti, R; Shabala, S; Zwaan, M; et al. (Oxford University Press, 2015)
We report the discovery of a new 21-cm H I absorption system using commissioning data from the Boolardy Engineering Test Array of the Australian Square Kilometre Array Pathfinder (ASKAP). Using the 711.5–1015.5 MHz band of ASKAP we were able to conduct a blind search for the 21-cm line in a continuous redshift range between z = 0.4 and 1.0, which has, until now, remained largely unexplored. The absorption line is detected at z = 0.44 towards the GHz-peaked spectrum radio source PKS B1740−517 and demonstrates ASKAP's excellent capability for performing a future wide-field survey for H I absorption at these redshifts. Optical spectroscopy and imaging using the Gemini-South telescope indicates that the H I gas is intrinsic to the host galaxy of the radio source. The narrow [O III] emission lines show clear double-peaked structure, indicating either large-scale outflow or rotation of the ionized gas. Archival data from the XMM–Newton satellite exhibit an absorbed X-ray spectrum that is consistent with a high column density obscuring medium around the active galactic nucleus. The H I absorption profile is complex, with four distinct components ranging in width from 5 to 300 km s−1 and fractional depths from 0.2 to 20 per cent. In addition to systemic H I gas, in a circumnuclear disc or ring structure aligned with the radio jet, we find evidence for a possible broad outflow of neutral gas moving at a radial velocity of v ∼ 300 km s−1. We infer that the expanding young radio source (tage ≈ 2500 yr) is cocooned within a dense medium and may be driving circumnuclear neutral gas in an outflow of ∼1 M⊙ yr−1.